2004
DOI: 10.1097/00129492-200403000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Is Perception of Handicap Related to Functional Performance in Persons with Vestibular Dysfunction?

Abstract: Patients who perceive a greater handicap as a result of dizziness demonstrate greater functional impairment than patients who perceive less handicap from dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
219
3
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(254 citation statements)
references
References 36 publications
18
219
3
14
Order By: Relevance
“…Contrary to the findings in the present study, correlation between functional impairment and perceived handicap has been shown in a tertiary balance outpatient centre, among patients with vestibular dysfunction [17]. The conflicting results may be due to the use of different balance measures and a marked difference in the selection of subjects, i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the findings in the present study, correlation between functional impairment and perceived handicap has been shown in a tertiary balance outpatient centre, among patients with vestibular dysfunction [17]. The conflicting results may be due to the use of different balance measures and a marked difference in the selection of subjects, i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Which of these to use depends on the context and on the condition of the patient. Dizziness and disturbances in balance have an impact on everyday life and correlation between functional impairment and perceived handicap among patients with vestibular dysfunction has been shown in a tertiary balance outpatient centre [17]. The correlation between impact on everyday life and disturbances in balance in primary care patients with dizziness has not, to our knowledge, been studied sufficiently.…”
mentioning
confidence: 91%
“…The postural instability complaint was present in most of the cases (84.0%); in agreement with the statement that vestibular disorder symptoms in BPPV patients include not only the vertigo and unbalance fits caused by a sudden change in head position, but there is also an increase in postural sway during the vertigo episodes 4 . The Brazilian version 17 of the Dizziness Handicap Inventory 16 used indicated a moderate influence (mean of 49.11 points) of symptoms in quality of life 23 , similarly to what was previously found (mean of 52.89 points) in BPPV patients before treatment 6 . The mean value of 7.24 points upon the dizziness analog scale 18 suggested severe dizziness in the series evaluated.…”
Section: Discussionsupporting
confidence: 77%
“…The same problem has been reported, adding that gait with the horizontal head movement was the most difficult to perform when compared to the head's vertical movement 30 . DGI tasks, which the head is in movement, in horizontal or vertical rotation are the most difficult to be performed and are more related to functional disability and falls 31 . With this study, we can see that the physiological decline observed during the aging process, associated to the onset of chronic peripheral vestibular dysfunction, may contribute together to the loss in body balance and functional capacity; however, it is important to stress the need to carry out new studies comparing the relationship of these parameters in the experimental and control groups, in other words, in the elderly with chronic peripheral vestibular dysfunctions and healthy elderly.…”
Section: Resultsmentioning
confidence: 99%